Factors influencing health service utilization among the elderly in Insein Township, Yangon Region - Min Min Hlaing, Sandar; Clara, Naw; Nanda Han, Aye (Makara Journal of Health Research, 2020)
Background: With the increasing needs of the aging population and the increasing prevalence of non-communicable diseases, assessment of the equity and accessibility of health care among the elderly has become important. Methods: A cross-sectional descriptive study was conducted from December 2018 to December 2019 among 225 elderly to describe the factors influencing health service utilization. Multistage sampling was applied, and structured questionnaire was used to interview the elderly. Chi-squared test and multiple logistic regression were performed in data analysis. Results: The average age of the respondents was 71.7 ± 8.17 years old, and 68.4% of the respondents utilized health services within a year. Although sex, health habit, and diagnosed chronic disease were associated with health service utilization in bivariate analysis, multiple logistic regression results reported that physical exercise [adjusted odd ratios (AOR) = 3.02, 95%CI: 1.07–8.53], financial support of family [AOR = 2.77, 95%CI: 1.00–7.69], perceived transportation cost [AOR = 0.08, 95%CI: 0.01–0.54], accessibility to health care personnel [AOR = 0.14, 95%CI: 0.04–0.50], and perceived health status [AOR = 0.03, 95%CI: 0.01–0.09] were predictors of health service utilization. Conclusion: This study highlighted the significant influence of perceived health status, financial support of family, perceived transportation cost, and accessibility to health care personnel referred to the possible indicators of health care inequality issues.